Randomised trial of block and replace vs dose titration thionamide in young people with thyrotoxicosis. Issue 6 (December 2020) - Wood, Claire L; Cole, Michael; Donaldson, Malcolm; Dunger, David B; Wood, Ruth; Morrison, Niamh; Matthews, John N S; Pearce, Simon H S; Cheetham, Timothy D
Abstract : Objective: First-line treatment of thyrotoxicosis in young people is thionamide anti-thyroid drug (ATD) in a blocking dose with levothyroxine replacement (block and replace, BR) or in a smaller dose tailored to render the patient euthyroid (dose titration, DT). Our objective was to determine which regimen provides more stable biochemical control. Design: A multi-centre phase III, open-label randomised trial comparing BR with DT in patients aged 2–17 years with newly diagnosed thyrotoxicosis at 15 UK centres. Methods: Patients were randomised shortly after diagnosis and treated for 3 years. The primary outcome was the percentage of serum thyroid-stimulating hormone (TSH) levels in the reference range between 6 months and 3 years. Secondary outcomes included the proportion of Free thyroxine (FT4) levels in the reference range, adverse event frequency and 4 years outcome (remission/relapse). Results: Eighty-two patients were randomised, with details on clinical course in 81 (62 Female); 40 were allocated to BR (41 DT). Three withdrew with one ineligible. The mean percentage of serum TSH within reference range was 60.2% in BR and 63.8% in DT patients; adjusted difference 4.3%, 95% CI (−7.8 to 16.4); P = 0.48. Proportions for FT4 were 79.2% in BR and 85.7% in DT patients; adjusted difference 6.8%, (−0.2 to 15.6); P = 0.13. Three patients developed neutropenia – all on BR. 6 BR and 10 DT patients were in remission at 4y. Conclusion: This randomised trial has shown no evidence to suggest that BR, when managing the young patient with thyrotoxicosis, is associated with improved biochemical stability when compared to DT.